2013
DOI: 10.1063/1.4818963
|View full text |Cite
|
Sign up to set email alerts
|

Predicted alternative structure for tantalum metal under high pressure and high temperature

Abstract: First-principles simulations have been performed to investigate the phase stability of tantalum metal under high pressure and high temperature (HPHT). We searched its low-energy structures globally using our developed multi-algorithm collaborative (MAC) crystal structure prediction technique. The body-centred cubic (bcc) was found to be stable at pressure up to 300 GPa. The previously reported ω and A15 structures were also reproduced successfully. More interestingly, we observed another phase (space group: Pn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Furthermore, the MGPT-MD simulations directly showed that hex-ω exhibits poor mechanical stability and partial transformation to bcc, suggesting that it would actually be mechanically unstable at all temperatures and pressures in an unconstrained environment. The mechanical instability of hex-ω has since been so confirmed with first-principles, finite-temperature latticedynamics calculations [17,18]. Thus, of the structures studied in Refs.…”
Section: A(ωt ) = A(ω Ref T ) − P( ′ ωmentioning
confidence: 65%
See 2 more Smart Citations
“…Furthermore, the MGPT-MD simulations directly showed that hex-ω exhibits poor mechanical stability and partial transformation to bcc, suggesting that it would actually be mechanically unstable at all temperatures and pressures in an unconstrained environment. The mechanical instability of hex-ω has since been so confirmed with first-principles, finite-temperature latticedynamics calculations [17,18]. Thus, of the structures studied in Refs.…”
Section: A(ωt ) = A(ω Ref T ) − P( ′ ωmentioning
confidence: 65%
“…12 as well as to the orthorhombic Pnma phase suggested by Yao and Klug [17] and by Liu et al [18]. In addition to treatment with MGPT potentials, the present free-energy method can also be adapted to other temperature-independent potentials, including GPT, BOP, EAM, and FS potentials among others, for suitable applications in relevant materials.…”
Section: F Metastable Fcc Free Energymentioning
confidence: 99%
See 1 more Smart Citation
“…The melting points are obtained by pursuing the steady solid-liquid coexistence phase. 24) at high pressure and high temperature is controversial, bcc phase has been proved to be the most stable phase at T ¼ 0 up to 300 GPa. In molecular dynamics simulation, it is really a hard work to choose a proper potential to describe the phase relation of Ta.…”
Section: Equilibrium Melting Temperaturementioning
confidence: 99%
“…On one hand, whether or not a solid-solid phase transition occurred before melting is a hot topic. Several possible phases, i.e., hex-x, [18][19][20][21] A15, 22,23 and pnma, 24 have been reported to be the possible competitive phases with bodycentered cubic (bcc) at high pressure and high temperature. However, no agreement has been reached among them at the moment.…”
Section: Introductionmentioning
confidence: 99%